Panorama actual del bitcóin. Una descripción práctica y jurídica de las criptomonedas en Colombia y Ecuador (Tema Central) - Valencia Marín, Franco Daniel (2021)
Bitcoin is a technology originated in 2009 that aims to implement a decentralized payment system between people. The present work is carried out in order to publicize this technology, which denotes importance due to the functionalities and opportunities it offers for all types of individuals, from those who seek a refuge of value for their assets, to those who wish to invest your money or simply understand how it works and use it on a day-to-day basis. This writing exposes the origins of Bitcoin, as well as its main characteristics and operation. In addition, it analyzes its advantages and disadvantages from a practical point of view and places special emphasis on the existing legal regulation around cryptocurrencies in Colombia and Ecuador. Through a descriptive methodology and using qualitative and quantitative tools, it was possible to determine a progressive growth of Bitcoin in recent years, not only in terms of value, but also of adoption and security. For this reason, both Colombia and Ecuador must adapt their legal regulations, in order to live up to the digital age in which we find ourselves and thereby take advantage of the benefits of this phenomenon instead of preventing its development.